Herbal activation of mammary gland; a comparative morphometrical & Biochemical analysis - Malak A Al-Yawer; Huda M Al-Khateeb; Fadhil A Al-Khafaji; Zuher R. Zahid (مجلة كلية الطب, 2007)
Seventy five adult virgin female Norway rats (60 experimental and 15 controls) were used to evaluate the effect of seeds of three herbs (Fennel, Cumin and Garden cress) on their mammary glands. Experimental animals were fed with these herbs (each type of herb seeds was given to twenty experimental rats) for fourteen days. Rats were sacrificed and mammary gland sections were obtained, stained then morphometrically assessed. Serum prolactin level was performed too. Results revealed that Garden cress seeds are the strongest lactogenic agent among the three. Both Fennel and Cumin seeds were shown to be very weak galactagogues.